Factors of (Self) Education of Adolescents Intercultural Sensitivity - Šaulienė, Valdonė (Pedagogika, 2015)
In this study the research problem can be formulated as the question: what adolescents’ ability to communicate with people from other cultures should be promoted in order to develop a full-fledged intercultural dialogue in the future? Aim – ascertain the factors of (self) education of adolescent’s intercultural sensitivity. The object of investigation – intercultural sensitivity of adolescents, as one of the most important aspects of modern national identity. In order to investigate the intercultural sensitivity was selected M. J. Bennett’s (1986, 2004) theoretical Model of the Development of Intercultural Sensitivity and intercultural sensitivity’s measurement tool called the Intercultural Sensitivity Scale (ISS) developed by G. M. Chen and W. J. Starosta (2000). Instrument (ISS) has been translated into the Lithuanian language and adapted to Lithuanian adolescents. According to the scientific literature article discussed: is the progress of ethnorelativism the premise of intercultural dialogue? The empirical data analysis allows to discuss about some strengthen / weakening external / internal factors of intercultural sensitivity of adolescents: the worldview and environmental influences. To promote intercultural sensitivity of adolescents and intercultural dialogue in the future should be drawn attention to those aspects: cognitive – to teach them their own culture, they should know how to represent it, by behavior, thinking attributes promote to recognize the signs of other cultures as well as the learning of foreign languages; emotional – to motivate them understand, respect and accept their own and other cultures, their differences, allowing to fid friends abroad, to promote interest to notice the diversity, avoiding stereotypes, prejudice; behavioral – increasing adolescents’ national identity, self-confidence in dealing with others and the courage to be themselves.